Rural-Urban Migration in Developing Countries : A Survey of Theoretical Predictions and Empirical Findings - Lall, Somik V. (World Bank, Washington, DC, 2012)
The migration of labor from rural to urban areas is an important part of the urbanization process in developing countries. Even though it has been the focus of abundant research over the past five decades, some key policy questions have not found clear answers yet. To what extent is internal migration a desirable phenomenon and under what circumstances? Should governments intervene and, if so, with what types of interventions? What should be their policy objectives? To shed light on these important issues, the authors survey the existing theoretical models and their conflicting policy implications and discuss the policies that may be justified based on recent relevant empirical studies. A key limitation is that much of the empirical literature does not provide structural tests of the theoretical models, but only provides partial findings that can support or invalidate intuitions and in that sense, support or invalidate the policy implications of the models. The authors' broad assessment of the literature is that migration can be beneficial or at least be turned into a beneficial phenomenon so that in general migration restrictions are not desirable. They also identify some data issues and research topics which merit further investigation.